A comprehensive study of load balancing approaches in real-time multi-core systems for mixed real-time tasks - Jadon, Shruti; Pradyuman, K.K.; Kalaria, Urmil; Varsha, K.R.; Gupta, Karthik; Honnavalli, Prasad B. (IEEE access, 2024)
Real-time systems are becoming pervasive with the growing global connectivity and rising consumer demands. The need for real-time processing has become a crucial part of many business applications worldwide. A key factor that determines the time taken for an application to give out the result hinges on its ability to prioritize, manage, and execute real-time workloads. However, there are several difficulties and constraints connected with implementing tasks in a real-time context. This research study primarily focuses on load balancing for mixed real-time tasks on a multi-core system, one of the major challenges for executing real-time workloads. The purpose of load balancing is to distribute the load evenly among the processor(s) and maximize their utility while minimizing overall execution time. Several algorithms have been implemented in theory to improve performance and efficiency by distributing the system workload across multiple nodes. The goal of this paper is to present a critical analysis of existing load-balancing techniques for both periodic and aperiodic tasks. The paper explores several factors, including throughput, performance, migration time, response time, overhead, resource utilization, scalability, fault tolerance, power efficiency, and other variables that play a crucial role in assessing the efficacy of load balancing in real-time systems. This study also identifies areas that warrant further exploration or investigation, suggesting potential avenues for future research, and highlighting emerging trends or developments that may shape the field.